"Grammatyka dla Polaków chcących się uczyć angielskiego języka" (1788) z historycznojęzykoznawczego punktu widzenia. Rekonesans badawczy = "Grammar for Poles who want to learn English language" (1788) from the perspective of diachronic linguistics. Research reconnaissance - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to enter into linguistic studies the text of the first textbook of English for Poles. Methodologically, the article uses the idea of diachronic studies, which deals with the history of using Polish language from the functional perspective. Handbook entitled "Grammatyka for Poles who want to learn English language" was written by an educated basilian monk Julian Antonovich and released in the royal printing in 1788.
Keywords: językoznawstwo stosowane; perspektywa diachroniczna; podręcznik; gramatyka; historia nauczania języka angielskiego; applied linguistics; diachronic perspective; handbook; grammar; history of teaching English